HEAT RATE SYSTEM ANALYSIS IN THE STEAM POWER PLANT IN NIITANASA USING ENVIRONMENTALLY FRIENDLY LOW-CALORIE FUELS (REVISI) - Hasanudin, La; Gunawan, Yuspian; Lolok, Agustinus; ., Salimin; ., Kadir; ., Samhuddin (MATTER: International Journal of Science and Technology, 2020)
The heat rate in a steam power plant is very important to know because it involves the amount of energy supply needed to produce electricity. This is done to determine the heat energy input from fuel needed in an electric energy. The purpose of this research is to analyze the heat rate needed in a steam power plant. The method used is the direct method, the required input is Gross kWh, Net kWh, coal fuel use, calorific value of the fuel. The type of fuel used is low calorie type of lignite. The results of the Gross Heat rate in January were seen 4,323.98 kcal / kWh while the Net Heat rate was 5,010.97 kcal / kWh. In December the Gross Heat rate was 4,141.72 kcal / kWh while the Net Heat rate was 4,992.96 kcal / kWh. This value is relatively high at a capacity of MW 100 MW.